SISTEM PELAYANAN WISUDA BERBASIS WEB DI UNIVERSITAS SAHID SURAKARTA - Mohan Adha Rifai; Dwi Retnoningsih; Firdhaus Hari Saputro Al Haris (JURNAL GAUNG INFORMATIKA, 2017)
The quality of an agency can be obtained in various ways such as by improving the quality of employee resources, training/education, structured work management as well as the management and care of good data. Currently, data management is essential for any institution, both government and private agencies, because basically all agencies working process requires data that will be processed and processed in a way to produce a report that will be used in accordance with their respective needs. Sahid University of Surakarta is one example of private educational institutions that need servicing and processing of structured data, such graduation data. Because they are still using semi manual procedure on the sistem, so that need takes a special system to do service graduation. The process of making "Graduation Service System" begins with an objectbased system design using UML, followed by building a database, system interface design for admin, students, and visitors. Then implemented in the major programming languages such as PHP, javascript and database such as MySQL.This graduation service system has been tested using the method WebQual to 30 people and resulted in the final calculation of the 77.4% value. Based on these results it can be concluded that the graduation service system is good and feasible to be implemented at Sahid University of Surakarta to do the processing, management and graduation data services to students in an integrated manner.